Comparative Religion Studies: Methodology and Methods of Research - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The article explores the basics of comparative religious studies, which becomes especially relevant in the age of globalization, in the context of exacerbation of many problems of a purely religious nature that lead to violence and tragedies. The importance of discourse-analysis as a method in research of the main characteristics of such a communicative phenomenon as religion is highlighted. Discourse-analysis is the study of features of the communicative phenomenon (religion), which acquire a discursive fixation of the religious and do not take into account the effects of confessional discourse, which have no sociological dimension. The aim and the tasks. That is why there is a need for a systematic analysis of religious discourse using the method of discourse analysis, which allows to objectively describe and explore the structural features of religious space. The following research methods were used: the method of historicism, the interdisciplinary method, the structural one, as well as the phenomenological and hermeneutic approaches. Research results. The substantive components of the terms "mythologema" and "theologema" are analyzed; the significance of such methods of comparative religious studies as systemic, historical, genetic, meaningful, ethical and emic is substantiated. Particular attention is paid to the interpretation of such concepts as "theology", "religion", "sacred", "prayer", "sacrament" and others, within the framework of comparative religious studies. Discussion. It is about defining the conceptual-commonality that exists in each religious tradition, giving the opportunity to consider religious phenomena in their original context, to describe them based on the use of precise criteria for the functioning of elements of religious discourse. The conclusion is that it is fundamentally important for comparative religious studies to reveal the process of becoming a semiotic space of religious discourse from mythological consciousness to modern theology. In our view, this approach allows us to uncover and correctly interpret spiritual, religious symbols, religious signs and meanings, which are an indication of religious faith and an incentive for the moral development of man. The notion of religion as a symbolic means of communication between man and higher reality allows us to take into account, first, the context of that communication, and second, its eternal content, which is independent of external influences.